Experimental study on effective bond length of basalt textile reinforced mortar strengthening system: Contributions of digital image correlation. (December 2018) - Caggegi, Carmelo; Sciuto, Denise; Cuomo, Massimo
Highlights: An experimental study on a basalt-TRM strengthening system has been carried out. Eight series of samples have been tested by Single Shear Tests. The effective bond length of the TRM strengthening system has been evaluated. The benefits of DIC in the identification of effective bond length have been defined. Abstract: Textile reinforced mortar (TRM) strengthening systems appear to be a preferred solution for reinforcing historical masonry structures. At present, the study of testing methods that are more appropriate for defining the mechanical design parameters is of major interest for the scientific community. The experimental research presented in this paper was carried out to define the effective bond length of a Basalt TRM system applied to a homogeneous substrate. In order to achieve this goal, several series of specimens, characterised by different bond lengths, were analysed by means of shear tests. The use of digital image correlation permitted the definition of the displacement and strain fields related to the reinforced specimen surfaces and an improved description of the debonding phenomena recorded during the tests.